Cryptocurrency Analysis Used as Marriage Dowry Based on the Views of Ulama in Asahan Regency - Ahmad Zakaria Hasibuan; Zainal Arifin Purba (al-Afkar, Journal For Islamic Studies, 2025)
This study aims to analyze the use of cryptocurrency as a dowry in a marriage contract based on the views of scholars in Asahan Regency. Cryptocurrency, as a form of digital currency that has no physical form and is not controlled by the state financial authority, has triggered a debate in the perspective of Islamic law, especially when used as a dowry which is an important pillar in the marriage contract. This research uses an empirical method with a qualitative approach. Data were obtained through in-depth interviews with scholars from various Islamic organizations in Asahan Regency, such as the local Indonesian Ulema Council (MUI), leaders of Islamic boarding schools, and other religious leaders. The results showed that the majority of scholars in Asahan Regency rejected the validity of cryptocurrency as a marriage dowry. The main reasons are the uncertainty of value (gharar), very high price fluctuations, and its uncertain legal status both in the state and sharia. Some scholars categorize it as a speculative tool and close to the elements of maisir (gambling), so it does not meet the requirements of assets that can be used as dowry according to Islamic law. However, there is a minority of views that are tolerant with a note: the cryptocurrency must be able to be measured in value clearly, mutually agreed upon, and does not contain elements of fraud. This study concludes that the aspects of clarity of value, usefulness, and legality are the main indicators of the scholars' assessment in determining the validity of an object as a dowry. Therefore, there is a need for a firmer and more uniform fatwa from religious authorities to provide legal and sharia certainty to the community.